The removal of sulfur dioxide, iron potassium from sulfited musts with ion exchange resins - Pezzi, Germano Mansueto; Fenocchio, Paolo (Pesquisa Agropecuaria Brasileira, 2014)
A comparison was made of ability of four ion exchange resins to remove sulfur dioxide, iron and potassium from sulfited musts. The resins used were Lewatit S 100 and MP 62 and Amberlite IR-120 and IR-45. The Lewatit MP 62 resin proved unsuitable for this purpose because it decolorized the must. Amberlite IR-120 and IR-45, removed 62-92% of the iron, 80-93% of the potassium, 50-59% of the free sulfur dioxide and 27-41% of the total sulfur dioxide without affecting the colour.